PENGARUH STRATEGI GREEN MARKETING DAN LABEL HALAL TERHADAP MINAT PEMBELIAN ULANG KONSUMEN PADA KONSUMEN FORE COFFE DI KOTA SURAKARTA - Ayatullah Muhammad Ibrahim; Muhammad Sholahuddin (JURNAL LENTERA BISNIS, 2025)
The objective of this research is to examine the effect of green marketing strategies and the presence of halal certification on consumers’ intention to repurchase Fore Coffee products in Surakarta. The target population comprises individuals who consume coffee in the Surakarta region. A purposive sampling method was employed to select participants, yielding a total sample size of 150 respondents. Data were collected through a structured questionnaire utilizing a Likert scale to measure responses. For the purpose of data analysis, the study adopted PLS methodology, facilitated through the SMARTPLS 4.0 software. The analytical framework of PLS-SEM encompasses two main components: the measurement model (outer model) and the structural model (inner model). The findings indicate that green marketing dimensions specifically green product, green price, green place, and green promotion exert a significant influence on consumers’ repurchase intentions. Moreover, the halal label is found to have a positive and statistically significant impact on repurchase behavior. This study has a novelty in combining green marketing mix strategies with halal labels in analyzing consumer repurchase intention, which has not been widely studied simultaneously. The focus on Fore Coffee in Surakarta City also provides a new perspective because similar studies are generally conducted in big cities. In addition, this study highlights repeat purchase behavior, not just initial purchase intention, and integrates environmental and religious values ​​in the unique context of Indonesian consumers.